Analisis Penerapan Debt to Equity Ratio Menurut Sak dan Peraturan Pajak sebagai Dasar Pemeriksaan Pajak - Milko Hutabarat; Marthauli Miranda Butar Butar; Agustina Indriani (AKUNTANSI 45, 2025)
This study aims to analyze the calculation of the Debt to Equity Ratio (DER) based on Financial Accounting Standards (SAK) and tax regulations in the context of tax audits. Differences in calculation methods between accounting and taxation often lead to discrepancies in determining deductible interest expenses. This study uses a qualitative descriptive approach by analyzing companies’ financial statements and relevant tax regulations. The results show that the calculation of DER according to SAK can differ from the calculation according to tax regulations, particularly regarding the recognition of equity and debt components. These differences affect the results of tax audits and the company’s tax obligations. Therefore, understanding both perspectives is important to ensure compliance and accuracy of financial reporting. In addition, this study also provides recommendations for companies to adjust calculations in accordance with applicable tax regulations to avoid potential tax problems in the future. A good understanding of accounting principles and tax regulations can support more transparent and accurate financial management.